Best damn Exchange, SQL and IIS book period - Walther, Henrik; Horninger, Mark.; Adams, Chris (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2007)
Exchange, SQL and IIS are at the core of most Microsoft enterprise servers. The 2007 releases of these products, along with the release of Windows Vista and Windows 2008 Server, represents the biggest overhaul of Windows enterprise products since Windows 2000. The dramatic changes to security tools and the addition of features that support "anywhere access" present IT professionals with a steep learning curve. Making certain that these products are configured to meet regulatory compliance requirements adds additionaly complexity to day-to-day management network management. The Best Damn Exchange, SQL and IIS Book Period delivers an all-in-one reference for Windows System Administrators deploying the 2007 releases of these core Microsoft servers. The coverage is comprehensive, and provides users with just about everything they need to manage a Windows enterprise server. Special Bonus coverage includes how to gather and analyze the many log files generated by these servers. Key Features: * All-in-one coverage includes Exchange, SQL, and IIS Servers * Integrated coverage on all key security features * Bonus coverage includes analyzing server logs and integrating Communicator 2007.
Installing Exchange Server 2007; Managing Recipients in Exchange Server 2007; Managing the Exchange 2007 Mailbox Server Role; Managing the Client Access Server; Managing the Hub Transport Server; Managing the Edge Transport Server; High Availability for Exchange 2007 Mailbox Servers; Disaster Recovery with Exchange Server 2007; Installation of IIS 7.0; The Extensible Core Server; Get Started with IIS 7.0?s Configuration; Administration of an IIS 7.0 Web Server; Diagnostics in IIS 7.0; SQL Server Surface Area Reduction; SQL Server Roles; SQL Server Authentication and Granular Access; SQL Server Schemas; SQL Server Password Policies; SQL Server Agent Roles; SQL Server Administrative Roles; Integrating Communicator 2007; Analyzing Server Logs.
Keywords: Microsoft Internet information server; SQL server; Microsoft Exchange server; Client/server computing; Microsoft Exchange server; Microsoft Internet information server; SQL server; Electronic books